If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying x + 121 = 4(x + -5) Reorder the terms: 121 + x = 4(x + -5) Reorder the terms: 121 + x = 4(-5 + x) 121 + x = (-5 * 4 + x * 4) 121 + x = (-20 + 4x) Solving 121 + x = -20 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 121 + x + -4x = -20 + 4x + -4x Combine like terms: x + -4x = -3x 121 + -3x = -20 + 4x + -4x Combine like terms: 4x + -4x = 0 121 + -3x = -20 + 0 121 + -3x = -20 Add '-121' to each side of the equation. 121 + -121 + -3x = -20 + -121 Combine like terms: 121 + -121 = 0 0 + -3x = -20 + -121 -3x = -20 + -121 Combine like terms: -20 + -121 = -141 -3x = -141 Divide each side by '-3'. x = 47 Simplifying x = 47

| 2z+5=13 | | 37-6x=13 | | a+10=1 | | 10x-17=7x+1 | | 3z+3=9 | | 2z=2 | | 10n=9n+22 | | 3x+36=11x-44 | | 151-4x=6x+21 | | 4x-2=11x-37 | | 10+g=10 | | 2x=-10 | | 6x+8=-24-10x | | 3x+10=52-3x | | -75-7x=8x+15 | | d-7=-9 | | a+12=20 | | 12-8x=80-36x | | -3x+5=-6+x | | 98-6x=12x+20 | | z+11=8 | | 5(x+7)=2x | | 61-6=8x+19 | | -29-3x=7-7x | | 112-4x=4x+8 | | 5x+12=-96-7x | | 6(2x-6)=24 | | -133-8x=7x+17 | | 7-8x=62-43x | | 4=7+x+6x | | 87-7x=20x+24 | | 5X+3Y=15 | | 1(9x-9)+4x= | | ED= | | 7x+5=2x+90 | | 13x-14=25 | | 4x=9x | | s=-4s+30 | | 9x-10=26 | | -4x-23=103 | | 7x+5=3x+8 | | 4.2+1.9n=-0.36 | | z-2=14 | | 1w=4 | | 3x-7-8x-7=4x-9x-17 | | 2(3x-5)=15 | | -7y-3=11 | | -5+7b=8b-6 | | 29=8x-35 | | 2x+29=10x-35 | | w+1=10 | | 1000x+240=600 | | 6(2x+9)-(5x-2)=-3+4x | | 2w+10=6 | | 2x-1=12x-81 | | 12x+6=30 | | -1w=-8 | | -5-7=-8 | | -7+3b=4b-8 | | -5q-7=-8 | | 5+11x=75+x | | -7-5q=3 | | w-4=11 | | 2x+11=75-6x | | 74-4x=9x+22 |